Peruvian consensus for the use of Magnetic Resonance Imaging in the diagnosis and follow-up of patients with Multiple Sclerosis - Caparó-Zamalloa, César (2022)
The use of Magnetic Resonance Imaging (MRI) in the diagnosis and follow-up of patients with Multiple Sclerosis (MS) has optimized the care of the affected patients. Several international working groups have tried to clarify and standardize the global use of MRI but, on many occasions, data are extrapolated from other regions, do not contemplate local realities or are difficult to implement. Objective: To reach a consensus on aspects related to the use of MRI in the diagnosis and follow-up of patients with MS in Peru. Material and Methods: A group of Peruvian experts (neurologists and radiologists) worked on the elaboration of the consensus using a remote survey round methodology. Results: The recommendations, established on the basis of published evidence and on the experts’ criteria, focused on the role of both, the conventional MRI techniques and the measurement of brain atrophy in MS patients both at the time of diagnosis and during the follow-up period. Conclusions: The consensual recommendations could potentially assist in the standardization and optimization of the care and follow-up of patients with MS in our country.